Penterjemahan unsur budaya dalam novel In Dubious Battle/Perjuangan Sia-Sia / Nadzirah Ramlee - Nadzirah , Ramlee (2017)
Translation is the process of transferring information from source language to target language. This study involves a process of translation of two different cultures and languages, the English and Malay language. The purpose of this study is to discuss the translation of cultural elements in terms of cultural classifications and translation procedures that consist in the English and Malay translated text. The main approach use in this study is based on the theory of culture introduced by Newmark (1988). The theory of cultural translation by Newmark is used as a fundamental basis in analyzing data to achieve the purpose of the study. This theory is also appropriate to examine the cultural classification and cultural translation procedures of the target language. The cultural elements in this theory are divided into ecology, material culture, social culture, social organization (political and administrative), and gestures and habits. In addition, findings on translation procedures illustrates several procedures that are being emphasize in the translation of source texts. The procedures of literal translation or direct translation are often used by translators in translating source text into target text. This method is the most appropriate in delivering messages of literature in terms of form and meaning. Therefore, the translation of a literature should be based on a method or procedure of translation to ensure the translation piece to be produced is high quality.